2022
DOI: 10.3390/buildings12101511
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Barriers and Key Success Factors for Renewable Energy Public-Private Partnership Projects: A Continental Analysis

Abstract: The global energy demand has been increasing and posing multiple challenges across the globe, including global warming, environmental pollution, and energy-sustainability issues. Thus, multiple countries have been adopting renewable-energy (RE) sources to provide clean, reliable, affordable, and sustainable energy. Previously, a number of renewable energy projects has been delivered in the form of a public–private partnership (PPP) to take advantage of the private sector’s investment, technology advancements, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 84 publications
(85 reference statements)
0
8
0
Order By: Relevance
“…Likewise, Reynaers (2014), summarizing the works of other authors, found that PPP projects lack transparency, and the information provided is often inadequate, inaccurate, or misleading. The research (Othman and Khallaf, 2022) covering different continents revealed that similar barriers exist everywhere, for example regulatory, political, and financial barriers to implementing renewable-energy projects.…”
Section: Public-private Partnerships: Building Resilience In Critical...mentioning
confidence: 99%
“…Likewise, Reynaers (2014), summarizing the works of other authors, found that PPP projects lack transparency, and the information provided is often inadequate, inaccurate, or misleading. The research (Othman and Khallaf, 2022) covering different continents revealed that similar barriers exist everywhere, for example regulatory, political, and financial barriers to implementing renewable-energy projects.…”
Section: Public-private Partnerships: Building Resilience In Critical...mentioning
confidence: 99%
“…Attracting foreign investment in renewable energy projects through favorable policies and regulations can boost development. Investment in grid expansion to accommodate renewable energy integration is essential [48]. Developing energy storage solutions can address intermittency challenges.…”
Section: Lack Of Financingmentioning
confidence: 99%
“…Relative Importance Index (RII) is a non-parametric technique widely used by construction and facilities management researchers for analyzing structured questionnaire responses for data involving ordinal measurement of attitudes. For this type of analysis, a calculated weighted average for each factor, divided by the upper scale of measurement, was adopted to provide an importance index [18,63,64]. The RII is calculated using Equation ( 1)…”
Section: Relative Importance Index (Rii)mentioning
confidence: 99%
“…Indeed, in contrast to previous literature we define a ranking between the most important barriers and levers using the Relative Importance Index (RII) approach. This method allows a comparison of the negative (barriers) and positive (levers) incentives for adoption, at two levels of the value chain [18], i.e., the farmer and the co-operative level. For this comparison, we conducted two surveys: one on 71 farmers and the other on 19 co-operatives.…”
Section: Introductionmentioning
confidence: 99%